Intracellular activation of trypsinogen in transgenic mice induces acute but not chronic pancreatitis. Issue 10 (6th April 2011) - Gaiser, Sebastian; Daniluk, Jaroslaw; Liu, Yan; Tsou, Lilian; Chu, Jun; Lee, Woojin; Longnecker, Daniel S; Logsdon, Craig D; Ji, Baoan
Abstract : Background and aims: Premature intra-acinar activation of trypsinogen is widely considered key for both the initiation of acute pancreatitis and the development of chronic pancreatitis. However, the biological consequences of intracellular trypsinogen activation have not been directly examined. To do so, a new mouse model was developed. Methods: Mice were engineered to conditionally express an endogenously activated trypsinogen within pancreatic acinar cells (PACE-tryp on ). Hallmarks of pancreatitis were determined and findings were correlated to the level (zygosity) and extent (temporal and spatial) of conditional PACE-tryp on expression. Furthermore, the impact of acinar cell death in PACE-tryp on mice was assessed and compared with a model of selective diphtheria toxin (DT)-mediated induction of acinar apoptosis. Results: Initiation of acute pancreatitis was observed with high (homozygous), but not low (heterozygous) levels of PACE-tryp on expression. Subtotal (maximal-rapid induction) but not limited (gradual-repetitive induction) conditional PACE-tryp on expression was associated with systemic complications and mortality. Rapid caspase-3 activation and apoptosis with delayed necrosis was observed, and loss of acinar cells led to replacement with fatty tissue. Chronic inflammation or fibrosis did not develop. Selective depletion of pancreatic acinar cells by apoptosis using DT evoked similar consequences. Conclusions: Intra-acinar activation of trypsinogen is sufficient to initiate acute pancreatitis. However, the primary response to intracellular trypsin activity is rapid induction of acinar cell death via apoptosis which facilitates resolution of the acute inflammation rather than causing chronic pancreatitis. This novel model provides a powerful tool to improve our understanding of basic mechanisms occurring during pancreatitis.